The Effect of Self-Control on Loan Repayment Decisions of Women Market Vendors in Mbeya Municipality, Tanzania - William Clifford Gomera; Magwana Ibrahim Ngollo (Universitas Airlangga, 2023)
Objective: This study aims to examine the effect of self-control on loan repayment decisions of women market vendors in Mbeya municipality, Tanzania. Design/Methods/Approach: This study employed a mixed research design. Primary data was collected via questionnaires and semi-structured interviews. A stratified random sampling technique was used to come up with a sample of 348 respondents selected from a population of 1741 women market vendors. Finally, descriptive statistics and regression analysis were utilized to process the collected data. Findings: The result of data analysis determined that self-control had a significant adverse effect on loan repayment decision Originality/Value: This study is unique since it studies self-control and loan repayment amongst women market vendors. The specificity of the set population allowed for a more in-depth and nuanced understanding of the experiences and challenges faced by this specific group of individuals hence deriving originality in this research. Practical/Policy implication: Findings are useful to policymakers and microcredit providers. Policymakers should promote activities and education that assist Tanzanians in attaining self-control. They should devise policies to make loans more affordable and easier to repay. Microcredit lenders should utilize subjective measures of self-control on loan applications as it is highly effective in enhancing repayment when coupled with high levels of financial literacy.